Phosphate increase during fatigue affects crossbridge kinetics in intact mouse muscle at physiological temperature. (8th May 2017) - Nocella, M.; Cecchi, G.; Colombini, B.
Abstract : Key points: Actomyosin ATP hydrolysis occurring during muscle contraction releases inorganic phosphate [Pi ] in the myoplasm. High [Pi ] reduces force and affects force kinetics in skinned muscle fibres at low temperature. These effects decrease at high temperature, raising the question of their importance under physiological conditions. This study provides the first analysis of the effects of Pi on muscle performance in intact mammalian fibres at physiological temperature. Myoplasmic [Pi ] was raised by fatiguing the fibres with a series of tetanic contractions. [Pi ] increase reduces muscular force mainly by decreasing the force of the single molecular motor, the crossbridge, and alters the crossbridge response to fast length perturbation indicating faster kinetics. These results are in agreement with schemes of actomyosin ATPase and the crossbridge cycle including a low‐ or no‐force state and show that fibre length changes perturb the Pi ‐sensitive force generation of the crossbridge cycle. Abstract: Actomyosin ATP hydrolysis during muscle contraction releases inorganic phosphate, increasing [Pi ] in the myoplasm. Experiments in skinned fibres at low temperature (10–12°C) have shown that [Pi ] increase depresses isometric force and alters the kinetics of actomyosin interaction. However, the effects of Pi decrease with temperature and this raises the question of the role of Pi under physiological conditions. The present experiments were performed to investigate this point. Intact fibre bundles isolated from the flexor digitorum brevis of C57BL/6 mice were stimulated with a series of tetanic contractions at 1.5 s intervals at 33°C. As show previously the most significant change induced by a bout of contractile activity similar to the initial 10 tetani of the series was an increase of [Pi ] without significant Ca 2+ or pH changes. Measurements of force, stiffness and responses to fast stretches and releases were therefore made on the 10th tetanus of the series and compared with control. We found that (i) tetanic force at the 10th tetanus was ∼20% smaller than control without a significant decrease of crossbridge stiffness; and (ii) the force recovery following quick stretches and releases was faster than in control. These results indicate that at physiological temperature the increase of [Pi ] occurring during early fatigue reduces tetanic force mainly by depressing the individual crossbridge force and accelerating crossbridge kinetics. Key points: Actomyosin ATP hydrolysis occurring during muscle contraction releases inorganic phosphate [Pi ] in the myoplasm. High [Pi ] reduces force and affects force kinetics in skinned muscle fibres at low temperature. These effects decrease at high temperature, raising the question of their importance under physiological conditions. This study provides the first analysis of the effects of Pi on muscle performance in intact mammalian fibres at physiological temperature. Myoplasmic [Pi ] was raised by fatiguing the fibres with a series of tetanic contractions. [Pi ] increase reduces muscular force mainly by decreasing the force of the single molecular motor, the crossbridge, and alters the crossbridge response to fast length perturbation indicating faster kinetics. These results are in agreement with schemes of actomyosin ATPase and the crossbridge cycle including a low‐ or no‐force state and show that fibre length changes perturb the Pi ‐sensitive force generation of the crossbridge cycle.